Efficacy of Manual Therapy in TemporomandibularJoint Disorders and Its Medium-and Long-TermEffects on Pain and Maximum Mouth Opening:A Systematic Review and Meta-Analysis - Herrera-Valencia, Andrés; Ruiz-Muñoz, María; Martín-Martín, Jaime; Cuesta-Vargas, Antonio; González-Sánchez, Manuel (MDPI, 2020)
The aim of this study was to conduct a systematic review of the medium- and long-term efficacy of manual therapy for temporomandibular joint disorders, alone or in combination with therapeutic exercise. Information was compiled from the PubMed, SCOPUS, Cochrane, SciELO and PEDro databases. The inclusion criteria were established: randomized controlled trials only; participants must present any kind of temporomandibular disorder; the treatments must include manual therapy in at least one of the experimental groups; a minimum of 3 months of follow-up; pain must be one of the primary or secondary outcomes; and the article must be available in English, Spanish, Italian, Portuguese or French. Six documents that fulfilled all the criteria were obtained for analysis, two of them considered low quality and four considered high quality. A significant improvement in pain and mouth opening compared to baseline was observed after manual therapy treatment. Manual therapy seems to be an effective treatment for temporomandibular disorders in the medium term, although the effect appears to decrease over time. However, when complemented with therapeutic exercise, these effects can be maintained in the long term. This review underlines the importance of manual therapy and therapeutic exercise for the medium- and long-term treatment of temporomandibular joint disorders in daily practice.
Keywords: Articulación temporomandibular; Joint; Manual therapy; Pain; Review; Temporomandibular